Systematic Literature Review : Peran Gaya Belajar dan Kemampuan Berpikir Kritis Siswa terhadap Prestasi Belajar Matematika - Shohwatun Nisa, Raida; Widiastuti A, T. Tutut; Zaini Aditya, Ade Hilda (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the role of learning styles and students' critical thinking skills inachieving mathematics learning achievement. This research method is a secondary researchmethod through the Systematic Literature Review (SLR) approach. A total of ten journal articleswere analyzed to identify the relationship between learning styles (visual, auditory, kinesthetic)and critical thinking skills with students' mathematics achievement. The results of the studyindicate that learning styles have a significant impact on mathematics learning achievement,where students who understand their learning styles tend to get better learning outcomes. Inaddition, critical thinking skills have also been shown to play an important role in improvingachievement, with students who have a high level of critical thinking being superior in solvingmathematics problems. This study recommends the development of learning methods thatpay attention to differences in individual learning styles and emphasize improving criticalthinking skills to improve student achievement.